Hubungan antara Aktivitas Antioksidan dan Antikanker - Andi Himyatul Hidayah; Annisa Fitriyani; Kartika Sari; Maulida Mutiah A (Pusat Riset dan Inovasi Nasional, 2023)
In this day and age there have been many treatments performed for patients with cancer. The use of radioactivity and surgery is one way of treating cancer. In addition to radioactive use and surgery, chemotherapy methods can also be done. Various kinds of cancer treatment in patients using chemotherapy drugs have very strong side effects. Its aim is to conduct literature on the relationship between antioxidant and anticancer activity. The data collection process was done manually which included information about the title of the research, the researcher, the name of the journal or conference, the year of publication and the results of the research. The results of this study provide a better understanding of antioxidant and anticancer activity. Antioxidants as free radical scavengers are one of the main factors needed to cause DNA mutations Keywords : In this day and age there have been many treatments performed for patients with cancer. The use of radioactivity and surgery is one way of treating cancer. In addition to radioactive use and surgery, chemotherapy methods can also be done. Various kinds of cancer treatment in patients using chemotherapy drugs have very strong side effects. Its aim is to conduct literature on the relationship between antioxidant and anticancer activity. The data collection process was done manually which included information about the title of the research, the researcher, the name of the journal or conference, the year of publication and the results of the research. The results of this study provide a better understanding of antioxidant and anticancer activity. Antioxidants as free radical scavengers are one of the main factors needed to cause DNA mutations Keywords : anticancer activity, antioxidant. , antioxidant.